Big Data guided Digital Petroleum Ecosystems for Visual Analytics and Knowledge Management - Nimmagadda, Shastri; Ochan, Andrew; Mani, Neel; Reiners, Torsten (2021)
The North West Shelf (NWS) interpreted as a Total Petroleum System (TPS), is Super Westralian Basin with active onshore and offshore basins through which shelf, - slope and deep-oceanic geological events are construed. In addition to their data associativity, TPS emerges with geographic connectivity through phenomena of digital petroleum ecosystem. The super basin has a multitude of sub-basins, each basin is associated with several petroleum systems and each system comprised of multiple oil and gas fields with either known or unknown areal extents. Such hierarchical ontologies make connections between attribute relationships of diverse petroleum systems. Besides, NWS has a scope of storing volumes of instances in a data-warehousing environment to analyse and motivate to create new business opportunities. Furthermore, the big exploration data, characterized as heterogeneous and multidimensional, can complicate the data integration process, precluding interpretation of data views, drawn from TPS metadata in new knowledge domains. The research objective is to develop an integrated framework that can unify the exploration and other interrelated multidisciplinary data into a holistic TPS metadata for visualization and valued interpretation. Petroleum digital ecosystem is prototyped as a digital oil field solution, with multitude of big data tools. Big data associated with elements and processes of petroleum systems are examined using prototype solutions. With conceptual framework of Digital Petroleum Ecosystems and Technologies (DPEST), we manage the interconnectivity between diverse petroleum systems and their linked basins. The ontology-based data warehousing and mining articulations ascertain the collaboration through data artefacts, the coexistence between different petroleum systems and their linked oil and gas fields that benefit the explorers. The connectivity between systems further facilitates us with presentable exploration data views, improvising visualization and interpretation. The metadata with meta-knowledge in diverse knowledge domains of digital petroleum ecosystems ensures the quality of untapped reservoirs and their associativity between Westralian basins.